Development and prospect of cultural landscape heritage preservation in China / Wu Yang Rui ... [et al.] - Wu, Yang Rui; Ahmad, Raziah; Mohd Fauzi, Amalina; Fitry, Muhamad Solehin; Abd Rahman, Faisal (UiTM Press, 2024)
Cultural landscape heritage has garnered increasing global attention since being recognised on the World Heritage List 32 years ago. With its 5,000-year cultural history, China has cultivated a multitude of cultural and natural heritage, yet only seven Chinese cultural landscape sites are listed as World Heritage. Without comprehensive study and protection measures, the value of these landscapes might not be fully realised. This paper aims to enhance the understanding and protection of China's cultural landscapes. The study employs summary, textual, and comparative analysis methods. It begins by reviewing the concepts and characteristics of cultural landscapes and cultural heritage. It then categorises global research on cultural landscape protection, with a focus on World Heritage applications. The legal protection status of China's cultural landscapes is examined, followed by a comparative analysis of protection measures in selected Asian and European countries, identifying effective practices and areas for improvement. The research highlights significant gaps in the protection of China's cultural landscapes. The findings underscore the importance of valuing cultural landscapes as vital components of natural heritage. The paper concludes by proposing four basic principles for the protection and development of China's cultural landscapes, aiming to enhance legislative measures, promote societal awareness, and provide a framework for future legal developments, ensuring the preservation of these landscapes for future generations.